Limiting the protein corona: A successful strategy for in vivo active targeting of anti-HER2 nanobody-functionalized nanostars. (April 2017) - D'Hollander, Antoine; Jans, Hilde; Velde, Greetje Vande; Verstraete, Charlotte; Massa, Sam; Devoogdt, Nick; Stakenborg, Tim; Muyldermans, Serge; Lagae, Liesbet; Himmelreich, Uwe
Abstract: Gold nanoparticles hold great promise as anti-cancer theranostic agents against cancer by actively targeting the tumor cells. As this potential has been supported numerously during in vitro experiments, the effective application is hampered by our limited understanding and control of the interactions within complex in vivo biological systems. When these nanoparticles are exposed to a biological environment, their surfaces become covered with proteins and biomolecules, referred to as the protein corona, reducing the active targeting capabilities. We demonstrate a chemical strategy to overcome this issue by reducing the protein corona's thickness by blocking the active groups of the self-assembled monolayer on gold nanostars. An optimal blocking agent, 2-mercapto ethanol, has been selected based on charge and length of the carbon chain. By using a nanobody as a biological ligand of the human epidermal growth factor 2 receptor (HER2), the active targeting is demonstrated in vitro and in vivo in an experimental tumor model by using darkfield microscopy and photoacoustic imaging. In this study, we have established gold nanostars as a conceivable theranostic agent with a specificity for HER2-positive tumors.